Clinical studies of glass ionomer cements: Part I - A twelve month clinical study comparing Zinc Phosphate Cement to Glass Ionomer - Fricker John P.; McLachlan Mark D. (Sciendo, 1985)
Zinc phosphate has long been the standard luting agent for the cementation of orthodontic bands. There has been recent interest in the use of glass ionomer cements for this purpose.